Learning Obstacles pada mendesain pembelajaran Pendidikan Pancasila mahasiswa pendididikan guru sekolah dasar - Tarmizi, Pebrian; Susanti, Atika; Darmansyah, Ady (Borobudur Educational Review, 2025)
A prospective teacher must be equipped with the ability to design lessons as one of the pedagogical competencies that should be possessed by future teachers. This study aims to gain an understanding of the learning obstacles in designing Pancasila education lessons for students in the Primary School Teacher Education program. The participants in this study are students from the Primary School Teacher Education program at the University of Bengkulu. The method used in this research is qualitative. The analysis of the ability to design Pancasila education lessons was conducted through tests and interviews. The results of this study show that the learning obstacles encountered in designing Pancasila education lessons consist of ontogenic obstacles (psychological, conceptual, and instrumental), didactical, and epistemological obstacles. The recommendation from this study is to design learning that stimulates students to become independent in their learning.